2014
DOI: 10.1186/1476-511x-13-144
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal disharmony accelerates the initiation of atherosclerosis in apoE knockout rats

Abstract: BackgroundPsychosocial stress is one of the risk factors for atherosclerosis. As occlusal disharmony induces psychological stress, we hypothesized that psychological stress by occlusal disharmony accelerates atherosclerosis. The aim of this study was to investigate the effects of occlusal disharmony on the initiation of atherosclerosis in apolipoprotein E (apoE) knockout rats.MethodsFourteen male apoE-knockout rats (age; 8 weeks) (Sprague–Dawley strain background) were divided into two groups of seven rats: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Different models of APOE-deficiency have been generated by various gene editing strategies in rats. These Apoe −/− rats display a range of atherosclerosis phenotypes, ranging from no detectable lesions, to very early signs of lipid deposition and atherosclerosis ( 55 , 56 , 153 , 154 ), at least as compared with Apoe −/− mice, to more advanced lesions ( 57 ). Thus, one Apoe −/− rat model exhibits an atherosclerosis phenotype similar to that of the Apoe −/− mice described above but lesion progression appears to be generally slower than that in the mouse.…”
Section: Animal Models Of Hypertriglyceridemia and Their Susceptibilimentioning
confidence: 99%
“…Different models of APOE-deficiency have been generated by various gene editing strategies in rats. These Apoe −/− rats display a range of atherosclerosis phenotypes, ranging from no detectable lesions, to very early signs of lipid deposition and atherosclerosis ( 55 , 56 , 153 , 154 ), at least as compared with Apoe −/− mice, to more advanced lesions ( 57 ). Thus, one Apoe −/− rat model exhibits an atherosclerosis phenotype similar to that of the Apoe −/− mice described above but lesion progression appears to be generally slower than that in the mouse.…”
Section: Animal Models Of Hypertriglyceridemia and Their Susceptibilimentioning
confidence: 99%
“…Today, the introduction of the nuclease techniques, such as Zinc Finger (ZF) 26 , Transcription Activator-Like Effector Nuclease (TALEN) 27 and recently Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR/Cas9) 28 have enabled easy gene deletion in species other than mice. In 2011, scientists at Sigma’s Advanced Genetic Engineering (SAGE) Labs created ApoE gene knockout ( Apoe −/− ) rats by the use of ZF technology 29 . Only limited data on Apoe −/− rats exist 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, scientists at Sigma’s Advanced Genetic Engineering (SAGE) Labs created ApoE gene knockout ( Apoe −/− ) rats by the use of ZF technology 29 . Only limited data on Apoe −/− rats exist 29 , 30 . In two previous studies describing Apoe −/− rat models 29 , 30 , very early fatty streak lesions were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, with the application of novel gene editing techniques (TALEN and CRISPR/Cas system) knockout rats can be produced quickly and efficiently. There were already reports about ApoE knockout rats [ 16 17 ] . The plasma cholesterol levels of ApoE KO rats were 1.5-fold higher than WT controls, but significantly lower than ApoE KO mice, which are consistent with the present data.…”
Section: Discussionmentioning
confidence: 99%